2008
DOI: 10.21071/az.v59i226.4736
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros ruminais de vacas leiteiras mantidas em pastagem tropical.

Abstract: Foram utilizadas quatro vacas, portadoras de cânula no rúmen para estudar dois níveis de suplementação concentrada (base na matéria seca): 2,7 e 5,4 kg/vaca/dia, respectivamente, baixo (BC) e alto concentrado (AC). As vacas foram mantidas em pastejo intermitente de capim-Coastcross no período de verão, com lotação de cinco unidades animal/ha. O concentrado, para os dois níveis de suplementação apresentou a mesma composição química e foi dividido em partes iguais, fornecidas no momento das ordenhas da manhã e d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Therefore, silage dry matter intake was not replaced by concentrate supply. Pimentel et al (1998) observed increased intake of sorghum silage, when supplemented with soybean meal in 20% of the dietary dry matter, and Mota et al (2010) verified a decrease in silage intake, when concentrate supply increased 2.7-5.3 kg cow -1 day -1 , in cows reared in coastcross pasture, during the rainy season. According to Moore et al (1997), at low supplementation rates, changes in silage intake can be both positive and negative, but for high supplementation rates, changes are always negative.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, silage dry matter intake was not replaced by concentrate supply. Pimentel et al (1998) observed increased intake of sorghum silage, when supplemented with soybean meal in 20% of the dietary dry matter, and Mota et al (2010) verified a decrease in silage intake, when concentrate supply increased 2.7-5.3 kg cow -1 day -1 , in cows reared in coastcross pasture, during the rainy season. According to Moore et al (1997), at low supplementation rates, changes in silage intake can be both positive and negative, but for high supplementation rates, changes are always negative.…”
Section: Resultsmentioning
confidence: 96%